Argyrophil cells in normal, hyperplastic, and neoplastic endometrium. Issue 4 (April 1984) - Sivridis, E; Buckley, C H; Fox, H
Abstract : Scanty argyrophil cells are present in a substantial proportion of normal endometria, particularly during the secretory stage of the cycle. Argyrophil cells are also present in the various types of hyperplastic endometria and are found in more than half of endometrial adenocarcinomas. In some endometrial neoplasms they are present in abundance, but tumours rich in such cells do not have any features suggestive of a carcinoid tumour and are morphologically identical to adenocarcinomas of similar grade which are devoid of argyrophil cells. Endometrial adenocarcinomas containing argyrophil cells tend to be well differentiated and tend not to invade deeply into the myometrium. It is suggested that Müllerian epithelial stem cells possess a potentiality for differentiation into APUD cells.